Smart skills : business writing - Forsyth, Patrick (Smart skills., 2018)
Breakdowns in communication are common enough, but when messages are put in writing, things can quickly go from bad to worse. A badly written message can return to haunt you; now or in the future. Business Writing offers proven, practical advice on how to put together a clear message in a manner that readers will want to read. It will help you recognize the dangers of poor writing, prepare and write an effective message fast, match your style to methods you use, be persuasive where necessary and deal with all types of documentation from a "simple" email to a long report. This guide includes checklists, examples and exercises, and allows you to tackle anything that must be put in writing with confidence that it will be effective, engaging, memorable and also reflect positively on you.